Nutritional therapy in patients with COVID-19: some considerations and scientific evidence (Research, Society and Development, 2021)
The present study aimed to review the literature on nutritional therapy in patients with COVID-19, highlighting some nutrients with functional potential that can benefit patients in responding to infection and recovery from the disease. It is a simple narrative review, developed from a bibliographic survey, reading of original articles and other reviews on the theme. The articles were retrieved from the PubMed, Scielo and Web of Science databases. The main elevated findings are that malnutrition is a frequent feature in patients infected with SARS-CoV-2, associated with increased morbidity and mortality. Scientific evidence confirms nutritional therapy as a determinant in the prognosis of patients with COVID-19, with recommendations for hyperprotein supply and adequate content of nutrients with functional potential, such as those considered immunomodulatory and anti-inflammatory. It is concluded that a nutritional therapy with an increased supply of protein and rich in immunonutrients, can improve the clinical prognosis of patients with COVID-19.